Systematic Literature Review: Impact Adopt IFRS Approach Earnings Management and Value Relevance - Natalia Fitria Revini Pranata; Raras Aroyo; Edo Agus Pratama (International Journal of Integrative Sciences, 2024)
By conducting a thorough literature analysis, this study seeks to close the research gap by assessing the effects of IFRS adoption on the profits management strategy and value relevance. This research method follows a systematic literature review process that consists of three main stages: planning the review, implementing the review, and reporting the review. A total of 28 articles were used for this systematic literature review based on inclusion and exclusion criteria. According to a comprehensive analysis of the literature covering all studies published in journals between 2017 and 2023, the implementation of IFRS has varying effects on value relevance and profits management strategies. With the convergence of IFRS, earnings management practices continue to occur. The impact of IFRS adoption also varies depending on factors such as company size, profitability, and institutional factors in developing countries. Relevant information in financial reports is considered very important for decision-making, and quantitative methods are considered more effective in examining the impact of IFRS adoption